2021
DOI: 10.1111/ijcp.14296
|View full text |Cite
|
Sign up to set email alerts
|

The agreement between arterial and venous lactate in patients with sepsis

Abstract: Sepsis is defined as life-threatening organ dysfunction caused by dysregulated host response to infection. Mismatch between oxygen supply and demand results in tissue hypoperfusion and hypoxia, leading to anaerobic metabolism and lactate production. 1 The importance of lactate levels for the diagnosis, prognostication, risk stratification and guidance to treatment is well established. 2 Thus, lactate is a defining criterion for sepsis and septic shock, and a key resuscitation target in the Surviving Sepsis Cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In severe cases, patients may have adverse symptoms, such as septic shock and multiple organ failure. This will seriously threaten the life and health of patients [ 2 ]. Therefore, early judgment and accurate evaluation of clinical sepsis can play a positive role in improving the prognosis and quality of life of patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, patients may have adverse symptoms, such as septic shock and multiple organ failure. This will seriously threaten the life and health of patients [ 2 ]. Therefore, early judgment and accurate evaluation of clinical sepsis can play a positive role in improving the prognosis and quality of life of patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial blood is the preferred sample for lactate measurement because it is derived from mixed venous blood and thus provides a representative sum of all sources of tissue lactate production. 39 Capillary blood, which is more easily obtained, is an alternative sample employed for lactate determination. In healthy volunteers or intensive care human patients, capillary lactate measurements were 47% higher than arterial blood lactate when sampled at the fingertip.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the correlation between ScvO 2 and the adverse prognosis of septic shock demonstrated that ScvO 2 levels were not associated with poor outcomes [29,30]. The importance of lactate levels for the diagnosis, prognostication, risk strati cation and guidance to treatment is well established [31].…”
Section: Discussionmentioning
confidence: 99%